2004
DOI: 10.1007/s00120-004-0532-7
|View full text |Cite
|
Sign up to set email alerts
|

Brennnesseltrockenextrakt (Bazoton � -uno) in der Langzeittherapie des benignen Prostatasyndroms (BPS)

Abstract: Phytotherapy of BPS has a long tradition in Germany; nevertheless, data referring to single phytotherapeutic agents are rare. We therefore performed a randomized, double-blind, placebo-controlled multicenter study for 1 year with Bazoton uno (459 mg dry extract of stinging nettle roots) with 246 patients. The IPSS decreased on average from 18.7+/-0.3 to 13.0+/-0.5 with a statistically significant difference compared to placebo (18.5+/-0.3 to 13.8+/-0.5; p=0.0233). The median Q(max) increased by 3.0+/-0.4 ml/s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 14 publications
0
4
1
Order By: Relevance
“…This response exceeds the rate of 43% reported by patients treated with herbal medicines in real-life practice in the TRIUMPH study [22]. The average IPSS reduction of 5.8 points that was achieved with pumpkin seed in the present study exceeds the placebo result by 1.4 points, whereas in studies of other herbal preparations, only a 1-point difference from placebo was observed [16,23]. The post-/pre-treatment ratio of 0.66 for the IPSS in the pumpkin seed group represents a fair response and almost reaches the level of 0.6 indicating a good response according to the efficacy grading of the International Consultation on BPH [24].…”
Section: Discussioncontrasting
confidence: 52%
“…This response exceeds the rate of 43% reported by patients treated with herbal medicines in real-life practice in the TRIUMPH study [22]. The average IPSS reduction of 5.8 points that was achieved with pumpkin seed in the present study exceeds the placebo result by 1.4 points, whereas in studies of other herbal preparations, only a 1-point difference from placebo was observed [16,23]. The post-/pre-treatment ratio of 0.66 for the IPSS in the pumpkin seed group represents a fair response and almost reaches the level of 0.6 indicating a good response according to the efficacy grading of the International Consultation on BPH [24].…”
Section: Discussioncontrasting
confidence: 52%
“…A few monoherbal plants have reduced IPSS. These include Serenoa repens Bartram [ 34 ], Urtica dioica L. [ 27 ], and Pteris multifida [ 28 ]. In the present study C. membranaceus ethanolic root extract (a monoherbal preparation) showed a significant reduction in total IPSS of the subjects at the end of the study period ( P = 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Other clinical studies carried out supported the use of phytotherapies from different plants such as Eviprostat (Matsumoto et al, 2010), Pygeum africanum extract (Chatelain et al, 1999), Stinging nettle root extract (Bazotonuno) (Schneider and Rübben, 2004), PR-2000 ( Tribulus terrestris ) (Sahu and Kumar, 2001), and others in the management of BPH but which are beyond the scope of this review as the actual polyphenols in these phytotherapies were not indicated in these studies.…”
Section: Clinical Studies/management Of Bph With Dietary Polyphenolsmentioning
confidence: 99%